2008
DOI: 10.1249/mss.0b013e3181586b2c
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Availability and Muscle Energy Metabolism during Intermittent Running

Abstract: These results suggest that CHO-E ingestion improves endurance capacity during intermittent high-intensity running in subjects with high preexercise muscle glycogen concentrations. The greater endurance capacity cannot be explained solely by differences in muscle glycogen, and it may actually be a consequence of the higher plasma glucose concentration towards the end of exercise that provided a sustained source of CHO for muscle metabolism and for the central nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
2
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 24 publications
7
56
2
6
Order By: Relevance
“…The significant influence of time on HR in this study is again in line with some previous adult work Morris et al 2003). Furthermore, the nonsignificant trend for a higher HR in the CHO trial has been observed in adult participants beginning the LIST in both glycogen depleted and supplemented states Foskett et al 2008). It appears that this trend cannot be explained by greater levels of dehydration or a greater work intensity in the CHO trial.…”
Section: Sprint Timessupporting
confidence: 92%
“…The significant influence of time on HR in this study is again in line with some previous adult work Morris et al 2003). Furthermore, the nonsignificant trend for a higher HR in the CHO trial has been observed in adult participants beginning the LIST in both glycogen depleted and supplemented states Foskett et al 2008). It appears that this trend cannot be explained by greater levels of dehydration or a greater work intensity in the CHO trial.…”
Section: Sprint Timessupporting
confidence: 92%
“…Other investigations supported the previous findings by observing that CHO consumption improved intermittent running capacity [61,62], soccer skill performance [63] and the distance covered during the second half of the game [64] when compared to a placebo beverage. The beneficial effects of CHO ingestion were associated with the maintenance of glycogen levels [61,65].…”
Section: Metabolic Stress Of Soccersupporting
confidence: 70%
“…However, other factors may be a consequence of the ergogenic effect of CHO ingestion. One explanation was associated to the enhanced fuel availability to the active muscles and Central Nervous System (CNS) as the result of the elevated plasma glucose concentrations [62]. Another mechanism could be ascribed to the lowered free fatty acid concentrations as the result of CHO ingestion.…”
Section: Metabolic Stress Of Soccermentioning
confidence: 99%
“…These laboratory and Weld tests are used to uncover the lack of control of the activity pattern and exercise intensity in a game, resulting from the randomized order of players' actions, thus allowing a standardized analysis of metabolic, biochemical and functional features of intermittent exercise. Among several intermittent Weld tests, the Loughborough Intermittent Shuttle Test (LIST) has been used to study the eVects of the ingestion of carbohydrate-electrolyte solutions or meals (Foskett et al 2008;Nicholas et al 1995Nicholas et al , 1999, Xuid ingestion and gastric emptying (Leiper et al 2005), muscle metabolism and temperature (Morris et al 2005), muscle soreness and damage (Thompson et al 1999), heat acclimatization protocols (Sunderland et al 2008), cryotherapy treatment against muscle damage (Bailey et al 2007), as well as the inXuence of antioxidants (Kingsley et al 2005; Thompson et al 2001a) on intermittent exercise performance and recovery with special reference to soccer. In fact, some authors have suggested that LIST is a Weld test that simulates the activity pattern and the workload imposed by soccer, i.e., was designed to mimic the activities performed and the distance covered in a typical soccer match (Bishop et al 1999;Nicholas et al 2000).…”
Section: Introductionmentioning
confidence: 99%